Artistic Interpretation Of Women's Spirit In The Stories Of Abdulla Qahhor - Abdivaliyev Obitjon Odiljonovich (Zien Journals, 2025)
The article analyzes the image of women and the problems associated with their psyche in the stories of Abdulla Kahhor, one of the most talented representatives of Uzbek prose of the 20 th century.The psyche of the characters in the writer's stories "Anor", "Dahshat" is studied.
Keywords: Uzbek prose; symbol; problem